Insulin resistance surrogate markers and risk of hyperuricemia among patients with and without coronary artery disease: a cross-sectional study - Ghorbani, Zeinab; Mirmohammadali, Seyedeh Nooshan; Shoaibinobarian, Nargeskhatoon; Rosenkranz, Sara K.; Arami, Samira; Hekmatdoost, Azita; Mahdavi-Roshan, Marjan (Frontiers in Nutrition, 2023)
Background: Although emerging evidence emphasizes the associations between both insulin resistance and hyperuricemia with coronary artery disease (CAD) risk, no definite relationship has yet been established. In this respect, time-efficient and affordable methods to estimate insulin resistance (IR) status, and to predict risk of hyperuricemia, are needed. Thus, the goal of this investigation was to examine the associations between IR, as assessed by novel surrogate markers (triglyceride-glucose (TyG) and TyG–body mass index (TyG-BMI)), and risk of hyperuricemia in patients with and without diagnosed CAD. Methods: This cross-sectional study used data from the medical records of 1170 patients who were referred to the cardiology outpatient clinic. Medical records, anthropometrics, and serum analytes were determined at the initial visit. Hyperuricemia was defined as serum uric acid≥5.6 mg/dl. IR was estimated through surrogate markers (TyG and TyG-BMI). Multiple regression analysis was performed to assess the relationship between these indices and odds of hyperuricemia among patients with and without CAD. Results: Overall, 814 angiographically-confirmed CAD cases (mean age (SD) =52(8)yrs) were compared with 356 patients without CAD (mean age (SD)=48(8)yr). There were positive associations between TyG and TyG-BMI indices and odds of hyperuricemia in CAD patients after controlling for confounders (adjusted odds ratio (aOR)=1.60; 95%CI: 1.02-2.51; P-value=0.036; and aOR=1.83; 95%CI: 1.24-2.70; P-value=0.002, third tertiles for TYG and TYG-BMI, respectively). Conclusion: The present findings suggest that higher levels of the IR surrogate markers, TyG and TyG-BMI, are associated with higher odds of hyperuricemia in patients with CAD. However, given the cross-sectional design of this study, the sensitivity and specificity of these novel markers could not be determined for confirming the diagnosis of IR and hyperuricemia, further studies are needed to determine such outcomes and to confirm the current findings.